Geology, in-situ resource-identification and engineering analysis of the Vernal crater area (Arabia Terra): A suitable Mars human landing site candidate. (April 2022) - Pajola, M.; Pozzobon, R.; Silvestro, S.; Salese, F.; Rossato, S.; Pompilio, L.; Munaretto, G.; Teodoro, L.; Kling, A.; Simioni, E.; Lucchetti, A.; Tornabene, L.L.; et al.
Abstract: A multidisciplinary study of an ancient area of Mars (Early to Late Noachian) located in Arabia Terra is presented, centred at 6°1′N, 354°54′ E and including the 55 ​km size Vernal crater. By means of different spatial scale imagery datasets and digital terrain models (MOLA, THEMIS, HRSC, CTX, CaSSIS and HiRISE), we prepare a high-resolution geological map of the study site. We highlight the different bedrock stratigraphy inside the Vernal crater which is of particular exobiological interest given the presence of putative ancient hot springs, as well as identifying multiple transverse aeolian ridges, inverted fracture networks and paleochannels, mounds, and a 58 ​m fresh crater located just outside Vernal crater rim. Within all low-latitude regions of Mars, the studied site presents the highest values (up to 16.0 ​wt%) of water equivalent hydrogen, hence suggesting that there is a widespread presence of in situ subsurface (at maximum depths of 1–2 ​m) natural resources, such as water ice and/or hydrated minerals. The equatorial location of the area results in the maximum surface temperature and the highest mean solar flux gatherable on the surface of the planet throughout the year. The interesting scientific case, coupled with the presence of in situ exploitable resources and the thorough accomplishment of all landing/roving engineering safety requirements, make the Vernal crater area a strong landing site candidate for future human exploration of Mars. Graphical abstract: Image 1 Highlights: ISRU and Human landing site candidate close to Mars equator. First high-resolution geological map of Vernal crater and its surroundings. Ancient hot springs exobiological potential. In situ subsurface resource identification. Engineering safety fulfilment and exploration zones characterization.